THE EFFECT OF EXTENSIVE READING AND LEARNING STYLE ON ACADEMIC WRITING COMPETENCY OF SEMESTER FIVE STUDENTS OF STKIP HAMZANWADI SELONG - ., Umar; SEKEN, KETUT; Artini, L. P. (Jurnal Pendidikan Bahasa Inggris, 2013)
The present study aimed at investigating the effect of extensive reading and learning style on studentsâ academic writing competency. This study used population sample, in the sense that all students in the population (60 students) were taken as sample. The experimental group and the control one were determined through a random sampling. The experimental study employed a 2 x 2 factorial post test only control group design. The instruments used to collect the data were an academic writing test and learning style questionnaires. The data were analyzed by using Two-Way ANOVA Statistic and Tukey Test. The study showed that there was no significant difference in academic writing competency between students who are assigned to do extensive reading and those who are not. However, extensive reading and learning style were found to be interactively influence students academic writing competency, revealing that there was a significant difference between the writing competency of independent students taught using extensive reading and those who are not. The implication is that the students with independent learning style effectively improve their writing competency through extensive reading activity. Â  Keywords: extensive reading, learning styles, and academic writing competency.